STUDI PENDAHULUAN: PENGEMBANGAN BOOKLET TUMBUHAN REMPAH DALAM MASAKAN KHAS PARIAMAN SEBAGAI SUPLEMEN PEMBELAJARAN BIOLOGI FASE E - Sw, Sri Jayanti; Ardi, Ardi; Rahmatika, Helsa (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to conduct a preliminary investigation on the development of a spice plant booklet used in traditional Pariaman cuisine as a supplementary learning resource for Biology in Phase E. Data were collected through initial observations regarding the potential use of the booklet in the learning process. The study was conducted to assess the relevance of the information in the booklet to Biology topics, particularly biodiversity and the benefits of spice plants. The results, based on a survey of students, indicated that 88.6% of the learners primarily use textbooks as learning sources, showing a lack of variation in learning media. This highlights the need for media that can facilitate students' understanding of biodiversity. Additionally, 90.9% of students strongly agreed with the development of a spice plant booklet containing local potential. Based on these findings, it can be concluded that the development of a spice plant booklet for traditional Pariaman cuisine is necessary as a supplementary tool for Biology learning in Phase E.